Thymus Growth and Fetal Immune Responses in Diabetic Pregnancies - Warncke, Katharina; Lickert, Ramona; Eitel, Stephanie; Gloning, Karl-Philipp; Bonifacio, Ezio; Sedlmeier, Eva-Maria; Becker, Petra; Knoop, Jan; Beyerlein, Andreas; Ziegler, Anette-Gabriele (Hormone and Metabolic Research, 2017)
Type 1 diabetes (T1D) during pregnancy possibly affects the development of the thymus and the maturation of the immune system in the offspring. The aim of the ImmunDiabRisk study was to investigate thymus growth and maternal and fetal immune responses in pregnancies with and without T1D. The thymus circumferences of the fetuses of pregnant women with T1D (n=49) and without diabetes (n=59) were measured using ultrasound around the 29th gestational week and standardized for gestational age. Simultaneously, the frequencies and total numbers of cell markers were analyzed by flow cytometry in maternal peripheral blood, and at birth in umbilical cord blood. The standardized circumference of the thymus was similar in fetuses of mothers with and without T1D (p=0.26). We observed higher numbers of FOXP3 Tregs, memory Tregs, erythrocytes, and lymphocytes in the cord blood from T1D pregnancies (p=0.01, p=0.002, p=0.002 and p=0.02, respectively). The frequencies of CD4+/CD8+ T cells correlated positively in maternal blood and umbilical cord blood of mother-child pairs, as did the levels of neutrophils (Spearman’s correlation coefficient r=0.43, p=0.02 for CD4+/CD8+ cells; r=0.46, p=0.03 for neutrophils), while no significant correlations were observed between thymus circumference and any cell markers in the child. Parts of the prenatal immune system seem to develop differently in the offspring of mothers with and without T1D. The correlation of Tregs between maternal blood and cord blood may indicate a significant cross-talk between the maternal and fetal immune system.
Keywords: type 1 diabetes; pregnancy; thymus; ultrasound; regulatory T cells